Experience in the treatment of long-gap esophageal atresia by intraluminal esophageal stretching elongation - Zhang, Ning; Wu, Wenjie; Zhuang, Yujia; Wang, Weipeng; Pan, Weihua; Wang, Jun (Frontiers in Pediatrics, 2024)
Objective: To summarize the experience with intraluminal esophageal stretching elongation (ILESE) in the successful treatment of long-gap esophageal atresia (LGEA) at a single center.Methods: Clinical data of 68 neonates who underwent LGEA between February 2015 and January 2022 were retrospectively analyzed. Four patients died of multiple associated severe malformations and did not undergo ILESE.Esophageal anastomosis was successfully performed in 60 cases (93.75%) and failed in 4 cases (6.25%) treated with ILESE. The ILESE techniques, esophageal reconstruction, results, postoperative complications, and follow -up treatment were analyzed.The beginning time of performing ILESE preoperation was 53.4±39.4 days after birth, and the age of esophageal reconstruction was 122.2±70.3 days after birth in 60 cases. The gap length of proximal and distal esophageal segments which were evaluated the first time at admission was 4.8±1.3 vertebral bodies, whereas the gap before anastomosis was -0.46±0.90 vertebral bodies. Among the patients with esophageal primary-anastomosis, 55 received thoracoscopic surgery, and 5 underwent thoracotomy in the ea rly stage. Of the 60 children with ILESE, 58 underwent end -to-end esophagostomy, of which 17 cases were combined with circular esophagotomy (livaditis), and 2 cases of esophageal lengthening were combined with the reversal of the ligulate loop of the proximal esophagus (flap). Overall, 59 cases were cured (98.3%), and 1 patient died of respiratory failure postoperatively. All patients were followed up for 7 to 96 months. Postoperative anastomotic leakage occurred in 16 patients (27.6%), all of whom were successfully treated conservatively. Anastomotic stenosis occurred in 49 cases (83.1%), all of which were successfully managed by non-surgical treatment, including 12.7±9.3 times of esophageal balloon dilatation and 2 cases of stent dilatation. Gastroesophageal reflux occurred in 44 patients (74.6%), including associated or acquired esophageal hiatal hernia in 22 patients, and Nissen fundoplication was performed in 17 patients. Conclusions: ILESE is an effective method for prolonging the proximal and distal esophagus of theLGEA to reconstruct esophageal continuity using its esophageal tissue, with an efficacy rate of 93.75%. Postoperative anastomotic stricture and gastroesophageal reflux are common and require long-term, standardized follow-up and treatment.